A Pet-ficação da natureza ou a idéia da physis no antropoceno. - Agostino Cera (Perspectiva Filosófica)
My paper deals with the topic “Physis in a post-Heideggerianphilosophy of technology”, by interpreting it as two topics or questions. By doing so, I have the opportunity to present two related sides of my philosophical work. The first side consists in a several years historical and theoretical work on the philosophy of technology, whichculminates in the proposal of a Philosophy of Technology in the Nominative Case (TECNOM). The second side is more recent and has to do with the philosophical implications of the Anthropocene and culminates in its reinterpretation/redefinition as Technocene. The two topics/questions around which move these pages are the following: 1) whatis (whathasbecome) the post-Heideggerianphilosophy of technology? 2) whatis the peculiar interpretation of physis in ourage (the idea of nature) expressed by the Anthropocene? With reference to the first question, in the Part I (After Heidegger, Beyond Heidegger. The Empirical Turn in the Philosophy of Technology) I will sketch an overview on the most recent developments in this area of studies, or better, a critical historicization of the post-Heideggerianphilosophy of technology, starting from the so-called empirical turn. My thesis is that the empirical turn gradually turned in to an ontophobic turn, namely a rejection of Heidegger’s legacy, which has produced a philosophical lack/deficit in the philosophy of technology, namely its genetivization. Ascountermovement against this ontophobic turn (i.e. as first step for the establishment of a “philosophy of technology in the nominative case”) I suggest a Heidegger-renaissance in the philosophy of technology. Moving from Heidegger’s assumption according to which the technischesZeitalter establishes the death of physis/nature, that is its definitive trasformation in to an object (Gegenstand) or standing-reserve (Bestand), in the Part II (After Physis, Beyond Physis. The Pet-ification of Nature)I will highlight a new form of reification of nature. This is the Pet-ification of Nature, a trans-objectualreification of it which takes place in the Anthropocene. More than a new geological epoch, with “Anthropocene” I mean the entelechy of the age of technology and thisiswhy I propose to call it Techno-cene. In the pet-ification of nature I see the accomplishment of the “disenchantment of the world” (Weber) as goal of the whole modernity. Pet-ification of nature’s main out come consists in an ethical paradox: the Paradox of Omni-responsibility, namely the overcoming of Hans Jonas’s imperative of responsibility as an ethical standard for philosophical thought over recent decades.